Estudio de la fauna del depósito tardoantiguo de la Calle del Duque 33 de Cartagena - Portí Durán, Mariana (Antigüedad y Cristianismo, 1991)
This investigation undertakes the study of the fauna found in a pit dated to the late Roman period located in the lot situated in the Calle del Duque, 33, Cartagena. In spite of the fact that the number of findings in not very great, the toponomic study of these has provided interesting information in regards to the identification of the domesticated species and also of the consumption and of the butchering techniques.